PEMBERDAYAAN MASYARAKAT TRUNYAN DALAM UPAYA PEMBERIAN PELAYANAN PRIMA DAN BERKELANJUTAN KEPADA WISATAWAN - Sudiarta, I Nyoman (Buletin Udayana Mengabdi; Vol 7 No 1 (2008): Volume 7 No.1 – April 2008, 2012)
ABSTRACT The activities of society services that funded by DIPA of udayana university with the title The Involvement of Trunyan Society to give sustain excellece service to the guests. It’s aim to increasing of ability of Trunyan Society in excellence service, that followed by 40 tourism stakeholders from Trunyan village such as: head, secretary and staff of Trunyan Village, Boat owners, and local guides. Its activities do, because of negatif image of Trunyan Village so many of tourists and travelt agents postpone to go there. The kinds of excellence service give to the participants including; discussion dan practical how to implemetation of excellence service to the guests so they will fell happy and satisfaction. My big question mark is why local guide and boat owners not give good service, and always make tourist trap in Trunyan village and in burrier, because they do not know how to give best service and make how to make guest satisfaction. Based on it, we hope they will be a good guide and servicer and always make tourist happy start they arrive at Kedisan harbour proceed to to Village and burrier and back home via Kedisan or Toya Bungkah.